Change in the composition of fauna associated with Pocillopora spp. (Scleractinia, Pocilloporidae) following transplantation - Chomitz Ray, Benjamin (2023)
Introduction: Associated fauna comprises most of the diversity of a coral reef and performs ecological functions essential to the reef’s survival. Since Pocillopora corals harbor an important associated fauna, reef restoration efforts are underway in Golfo Dulce, Costa Rica, to preserve them. Objective: To describe changes in cryptofauna and fish communities associated with Pocillopora colonies to better understand the succession of associated fauna following transplantation. Methods: An experimental patch of 30 nursery-grown Pocillopora colonies and a control patch containing no colonies were monitored for 8 months following transplantation in Golfo Dulce. Cryptofauna within each colony and fish within each patch were observed using SCUBA to quantify temporal changes in the abundance, diversity, and community structure of the colonies. Results: The abundance and diversity of cryptofauna increased throughout the experiment. Obligate symbiont decapods were the most abundant. The composition of the community of cryptofauna differed between periods with fish in the genus Scarus as the main contributor to any differences. The increase in abundance and diversity of cryptofauna and fish may reflect coral growth and the corresponding availability of space and environmental complexity in the experimental patch. The composition of the cryptofauna communities was generally consistent with other studies. However, a high density of decapod symbionts could suggest that without other Pocillopora colonies to move to, they may crowd together despite their aggressive tendencies. Conclusions: Pocillopora colonies will experience an increase in symbionts that could positively contribute to the health and survival of the coral following transplantation.